The Role of Confocal Endomicroscopy in the Diagnosis and Management of Pancreatic Cysts - Margaret G Keane; Stephen P Pereira (European Medical Journal, 2021)
Pancreatic cystic lesions are an increasingly common clinical finding. Current diagnostic techniques cannot reliably differentiate patients with high-risk lesions requiring surgical resection from those that can be safely surveyed or discharged. As a result, some patients may undergo unnecessary surgery with associated morbidity while others enter long-term surveillance with associated healthcare costs. Needle-based confocal laser endomicroscopy enables real time microscopic examination of the epithelial lining of a cyst wall at the time of a standard endoscopic ultrasound examination. The procedure is associated with low rates of adverse events, especially when the probe is loaded into the fine-needle aspiration needle before the procedure and examination times are limited. Needle-based confocal laser endomicroscopy has consistently been shown to have better diagnostic accuracy than cytology, which is often paucicellular and non-diagnostic in pancreatic cystic lesions. Studies have shown that diagnostic accuracy in needle-based confocal laser endomicroscopy is 84–95% in mucinous lesions and 39–99% in serous lesions. However, this technology is expensive and its place in diagnostic algorithms remains uncertain. Despite this, health economic analyses in certain health systems have been favourable, largely because of its potential to be able to discharge patients with benign lesions, such as serous cystic neoplasms, from long-term surveillance. Widespread adoption of this technology is unlikely but it has the potential to have an important role in indeterminate pancreatic cystic lesions.